Design and modeling of solenoid inductor integrated with FeNiCo in high frequency - Abdelhadi Namoune; Rachid Taleb; Noureddine Mansour (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this work, the design and modeling of the solenoid inductor are discussed. The layout of integrated inductors with magnetic cores and their geometrical parameters are developed. The quality factor Q and inductance value L are extracted from the S-parameters and plotted versus frequency. The effect of solenoid inductor geometry on inductance and quality factor are studied via simulation using MATLAB. The solenoid inductor geometry parameters considered are the number of turns, length of the magnetic core, the width of a magnetic core, the gap between turns, the thickness of the magnetic core, the thickness of the coil and oxide thickness of solenoid inductor. The performance of the proposed solenoid inductor integrated with FeNiCo is compared with other solenoid inductors.